Placement of removable metal biliary stent in post-orthotopic liver transplantation anastomotic stricture - Tee, Hoi-Poh (The WJG Press and Baishideng, 2010)
Postoperative biliary strictures are the most common cause of benign biliary stricture in Western countries, secondary to either operative injury or bile duct anastomotic stricture following orthotopic liver transplantation (OLT). Surgery or endoscopic interventions are the mainstay of treatment for benign biliary strictures. We aim to report the outcome of 2 patients with refractory anastomotic biliary stricture post-OLT, who had successful temporary placement of a prototype removable covered self-expandable metal stent (RCSEMS). These 2 patients (both men, aged 44 and 53 years) were given temporary placement of a prototype RCSEMS (8.5 Fr gauge delivery system, 8 mm × 40 mm stent dimensions) in the common bile duct across the biliary stricture. There was no morbidity associated with stent placement and removal in these 2 cases. Clinical parameters improved after the RCSEMS placement. Long-term biliary patency was achieved in both the patients. No further biliary intervention was required within 14 and 18 mo follow-up after stent removal.